2018
DOI: 10.1093/cercor/bhx361
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Responses to Input From Distant Areas are Modulated by Local Spontaneous Alpha/Beta Oscillations

Abstract: Any given area in human cortex may receive input from multiple, functionally heterogeneous areas, potentially representing different processing threads. Alpha (8-13 Hz) and beta oscillations (13-20 Hz) have been hypothesized by other investigators to gate local cortical processing, but their influence on cortical responses to input from other cortical areas is unknown. To study this, we measured the effect of local oscillatory power and phase on cortical responses elicited by single-pulse electrical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…CCEPs are recorded from remote cortical areas and are presumed to reflect orthodromic propagation of the stimulus signal through the cortico-cortical connections ( Matsumoto et al 2017 ; Matsumoto and Kunieda 2018 ). This method was first applied in patients with implanted subdural electrodes and successfully delineated various functional cortical networks ( Matsumoto et al 2004 ; Lacruz et al 2007 ; Conner et al 2011 ; Koubeissi et al 2012 ; Swann et al 2012 ; Kubota et al 2013 ; Matsuzaki et al 2013 ; Keller et al 2014a ; Enatsu et al 2015 ; Usami et al 2018 ). The connectivity pattern retrieved as CCEPs overlaps in large part with the resting-state functional connectivity measured by resting-state fMRI ( Keller et al 2011 , 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…CCEPs are recorded from remote cortical areas and are presumed to reflect orthodromic propagation of the stimulus signal through the cortico-cortical connections ( Matsumoto et al 2017 ; Matsumoto and Kunieda 2018 ). This method was first applied in patients with implanted subdural electrodes and successfully delineated various functional cortical networks ( Matsumoto et al 2004 ; Lacruz et al 2007 ; Conner et al 2011 ; Koubeissi et al 2012 ; Swann et al 2012 ; Kubota et al 2013 ; Matsuzaki et al 2013 ; Keller et al 2014a ; Enatsu et al 2015 ; Usami et al 2018 ). The connectivity pattern retrieved as CCEPs overlaps in large part with the resting-state functional connectivity measured by resting-state fMRI ( Keller et al 2011 , 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested that oscillations shape the spatiotemporal patterns of neural activity in an efficient way that, in short time-scales, promotes short-term plasticity that facilitates attentional selection of particular stimuli or actions [23] and, over longer time-scales, promotes long-term plasticity needed for skill learning [10]. A recent study in humans showed that the amplitude of alpha and beta oscillations modulates the corticocortical evoked responses [24]. However, an association between oscillations and synaptic plasticity has not been demonstrated in the neocortex of awake animals.…”
Section: Introductionmentioning
confidence: 99%
“…HG activity is also widely used as an index of changes in neuronal population firing rates [17][18][19]. Thus, a CCSR HG induced by SPES reflects changes in neuronal firing rates elicited by simulated external input, via direct or indirect anatomical connections with the stimulation site [9,[20][21][22][23][24][25][26]. CCSR HG generator mechanisms are still debated [27], but the changes in neural behavior reported in stimulation studies with single unit recordings or dye imaging are similar to those of CCSR HG [28][29][30].…”
Section: Introductionmentioning
confidence: 99%